(3TQM JMaI GdCMHGHs - (3YHO Gddg Hf HgGA GdOjf eMeO Hf YHO Gddg GdTfThQi GdTGaYjs; (3HOQ GdOjf CHh GdbGSe eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbj SHW GdeGQOjfj, SHW GdeGQOjfj,J (B907 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU GdYdeGA HChaQ ebGe hHYO ajbhd YHO Gddg GdTfThQi gPG TQM eNJUQ Ydi GdeNJUQ GdeSei JMaI GdCMHGH ddTjN SHW GdeGQOjfi s
(3BNQgG (B:s
(3hEPG HSWJ GdCKfjf hGdKdGKjf YTQGJ aGdLhGH SJI hYTQhf hKdKGf gPG eG jSQg Gddg ef GdTQM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B1 (3U` (B361 (3Cf JMaI GdCMHGH ai Yde GdMSGH gi deDdagG HOQ GdOjf eMeO Hf eMeO Hf CMeO SHW GdeGQOjfi (B!s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs